2015
DOI: 10.5539/gjhs.v8n5p160
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Improved Prenatal Screening: A Narrative Review

Abstract: Background:Prenatal screening deals with the detection of structural and functional abnormalities in the fetus. Health care providers can minimize unintended pregnancy outcomes by providing proper counseling and performing prenatal screening. The purpose of the present review study is to investigate factors affecting improved prenatal screening.Methods:The present study is a narrative review searching public databases such as Google Scholar and specialized databases such as Pubmed, Magiran, Scientific Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Trials investigating the acceptance of non-invasive prenatal testing (NIPT) with cell-free fetal DNA mostly confirmed that uptake was clearly related to reimbursement by insurance companies or the national health system 15 , 34 . Other factors affecting the uptake of aneuploidy screening include counseling, the level of maternal education and trust in the healthcare provider as well as test-specific reasons such as maternal age, religious beliefs and the availability and acceptance of termination of pregnancy 29 , 30 , 32 , 35 – 38 . To date, there are no studies published which have investigated the acceptance of first trimester combined screening for PE in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trials investigating the acceptance of non-invasive prenatal testing (NIPT) with cell-free fetal DNA mostly confirmed that uptake was clearly related to reimbursement by insurance companies or the national health system 15 , 34 . Other factors affecting the uptake of aneuploidy screening include counseling, the level of maternal education and trust in the healthcare provider as well as test-specific reasons such as maternal age, religious beliefs and the availability and acceptance of termination of pregnancy 29 , 30 , 32 , 35 – 38 . To date, there are no studies published which have investigated the acceptance of first trimester combined screening for PE in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Women who declined screening had a lower BMI, which correlates with a lower risk for PE [27,28]. Maternal age is a risk factor for PE and trisomies; while advanced maternal age leads to an increased acceptance of aneuploidy screening, no such association was found for PE screening [29,30]. This can be explained by the fact that the screening rate for PE decreased with higher parity, which is linked to maternal age.…”
Section: Reason N (%) % Of Total Populationmentioning
confidence: 98%
“…Screening and risk assessment as part of preconception care helps to assess and gauge a holistic picture of the risk factors that can adversely affect perinatal outcomes [18]. Evidence suggests that perinatal screening and risk assessment help identify the trend of perinatal mortality [19], congenital anomalies [20,21], and general health [21]. Family planning, psychosocial counseling, empowerment of women, health promotion, and education are also important components of preconception care, which aim to increase awareness and modify an individual's behavior, preventing risky behaviors such as substance abuse and unsafe sex [7].…”
Section: Introductionmentioning
confidence: 99%